MEMPREDIKSI FINANCIAL DISTRESS DENGAN BINARY LOGIT REGRESSION PERUSAHAAN TELEKOMUNIKASI - Tiara Widya Antikasari; Djuminah Djuminah (University of Merdeka Malang, 2017)
In this globalization era, sub-sector telecommunication industry has rapid development as time goes by with the number of customers’ growth. However, its growth is not balanced with operational revenue development. Therefore, it is important to analyze the financial distress in telecommunication companies in order to avoid bankruptcy. This research aimed to investigate the effect of financial ratios to predict the probability of financial distress. Financial ratios indicator used profitability ratio, liquidity ratio, activity ratio, and leverage ratio. The population in this research was telecommunication companies listed in the Indonesia Stock Exchange periods 2009-2016. Based on purposive sampling method, the criteria of financial distress in this study was measured by using net operation negative two years, while statistic analysis used was logistic regression with a significance level of 10%. The result was that liquidity ratio (current ratio) and activity ratio (total asset turnover ratio) had a negative significant value, and profitability ratio(return on asset) and a leverage ratio (debt to total asset) had positive significant value to predict financial distress.